Analisis sistem taruhan dalam permainan rolet menggunakan simulasi - Liong, Choong Yeun; Choo, Jia Yuan; Zainol Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
Some people believe that certain betting systems that are often used in the roulette game may help them to make money from the casino. The purpose of this research is to demonstrate that no monetary gain is achieved from a roulette game based on the outcomes of a simulation study using six popular betting systems. The distribution of net monies gained is studied in order to evaluate the performance of the betting systems. Under the assumption that the net monies of zero as an indication of a break-even, the distribution of the net monies is studied based on a 95% confidence interval about zero. Since the upper and lower limits of all the confidence intervals are negative, particularly for the case of the cancellation system, this research found that all the betting systems considered are just a gimmick and a waste of money